Efl Students’ Engagement in Google Classroom Based-Literature Circle - Dewi, Liliana Sandra; Saefullah, Hilmansyah (STKIP Yapis Dompu, 2022)
This research reports on the findings of a case study on the application of Google Classroom based literature circle in an EFL reading class. The purpose of this study is to investigate EFL students' engagement in an online collaborative learning via Google Classroom-based literature circle. Based on data analysis from observation and questionnaires of three EFL students’ volunteers, the results revealed that the students are actively engaged in their own roles in the literature circle, such as leading the discussion in group by giving questions about the text, responding to the questions, sharing ideas and opinions, and retelling the story. This study found that students were enthusiastic about the Google Classroom-based literature circle. The implication of this study can contribute the teacher as alternative to implement online collaborative learning in reading classroom.